2020
DOI: 10.1111/1462-2920.15101
|View full text |Cite
|
Sign up to set email alerts
|

The key iron assimilation genesClFTR1,ClNPS6were crucial for virulence ofCurvularia lunatavia initiating its appressorium formation and virulence factors

Abstract: Summary Iron is virtually an essential nutrient for all organisms, to understand how iron contributes to virulence of plant pathogenic fungi, we identified ClFTR1 and ClNPS6 in maize pathogen Curvularia lunata (Cochliobolus lunatus) in this study. Disruption of ClNPS6 significantly impaired siderophore biosynthesis. ClFTR1 and ClNPS6 did mediate oxidative stress but had no significant impact on vegetative growth, conidiation, cell wall integrity and sexual reproduction. Conidial germination delayed and appress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Compared to wild-type (WT) CX-3, the Clftr1 deletion mutants caused delayed conidial germination and were reduced in appressoria formation. In addition, ∆Clftr1 and ∆Clnps6 mutants showed downregulation of several genes that were responsible for conidial germination, appressoria formation, non-host selective toxin biosynthesis, and cell wall-degrading enzymes [102]. ClNOX2-derived ROS signaling pathway and the ClM1-mediated CWI signaling pathway are involved in DHN melanin biosynthesis as a cross-linked manner.…”
Section: Other Fungimentioning
confidence: 98%
See 1 more Smart Citation
“…Compared to wild-type (WT) CX-3, the Clftr1 deletion mutants caused delayed conidial germination and were reduced in appressoria formation. In addition, ∆Clftr1 and ∆Clnps6 mutants showed downregulation of several genes that were responsible for conidial germination, appressoria formation, non-host selective toxin biosynthesis, and cell wall-degrading enzymes [102]. ClNOX2-derived ROS signaling pathway and the ClM1-mediated CWI signaling pathway are involved in DHN melanin biosynthesis as a cross-linked manner.…”
Section: Other Fungimentioning
confidence: 98%
“…Curvularia lunata is the pathogen that causes maize curvularia leaf spot disease. Iron assimilation gene ClFTR1 had been found to regulate the formation of appressoria [102]. Another study showed that ClM1 regulated the ClBRN1 transcriptionally and negatively regulated ClNOX2 transcriptionally, while ClNOX2 regulated the transcription of ClSCD1.…”
Section: Other Fungimentioning
confidence: 99%
“…Our previous work revealed that the RIA pathway is involved in the formation of the infection structures in the biotrophic stage and that the SIA pathway regulates the activity of virulence factors in the necrotrophic stage during C. lunata infection (Lu et al, 2020).…”
Section: Srec Is Essential For Transition Of Trophic Stages and Devel...mentioning
confidence: 99%
“…Transition from the asymptomatic biotrophic phase, characterized by intercellular thick primary hyphae, to the destructive necrotrophic phase, characterized by thin filamentous secondary hyphae, is referred to as the biotrophy-necrotrophy switch of hemibiotrophic fungi (Lee & Rose, 2010). Our previous study found that the transition from the biotrophic phase to necrotrophic phase at 24 h post-inoculation (hpi) matches the switch of iron assimilation pathways, which permits full virulence of C. lunata (Lu et al, 2020). Here, we show that C. lunata is exposed to drastic changes of the host iron environments during infection.…”
mentioning
confidence: 99%
“…Iron is an essential nutrient for maintaining the virulence of C. lunata. Lu et al 68 demonstrated that nonribosomal peptide synthetase 6 (ClNPS6) (GenBank accession: JQ698337.1) and Fe transporter permease (ClFTR1) (GenBank accession: AHN52042.1) were involved in the iron acquisition and shown to be essential for virulence in infectious stages of C. lunata.…”
Section: Toxins and Melaninmentioning
confidence: 99%